Análise do envelhecimento de membranas de borracha natural incorporadas com extrato de Copaifera oblongifolia - Hochberger, Luana Caroline (2022)
Natural rubber (NR), derived from the latex of Hevea brasiliensis, has important properties for biomedical applications. This polymer matrix acts as a controlled release system for incorporated bioactives, such as the extract of Copaifera oblongifolia fruits. However, aspects of the aging of this biomaterial on changes in functionality, structure and composition have received little attention. The objective was to evaluate the aging process of natural rubber membranes with copaiba (NRC) submitted to controlled conditions of time, luminosity and presence of oxygen. The NRC membranes were made and stored in the presence or absence of light, under vacuum or without vacuum, for periods of 30, 60 and 90 days. Subsequently, the NRC membranes were characterized. After analysis of the contact angle, it was observed that the NRC membranes both at time zero and at aging time were hydrophilic. The membranes were also thermally stable, observed through thermogravimetric analysis and differential exploratory analysis. In scanning electron microscopy, no morphological changes were observed. The membranes after 90 days packaged showed satisfactory antioxidant capacity. It is concluded that the membranes were resistant to the storage period, as they maintained their chemical, thermal, morphological and antioxidant characteristics, being another indication of a possible dressing for biomedical applications.